2022
DOI: 10.4314/jsasa.v55i.7
|View full text |Cite
|
Sign up to set email alerts
|

Application of ARMA information governance maturity model for assessment of records management programme at Chancellor College, University of Malawi

Abstract: Institutions, whether public or private, create records in the course of conducting their business. Records constitute a vital resource for any organisation, including universities. They are important as they provide the information needed by decision-makers and promote accountability. This study assessed the records management programme at Chancellor College, Malawi, using the ARMA Information Governance Maturity Model. Data for the study were collected through face-to-face interviews with purposively selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Data was solicited through interviews from ICT directorates and offices of registrars, and the findings are consistent with the other studies cited above. The study reported that ICT initiatives, including student information management systems, integrated library management systems and financial management systems, are used in creating and capturing records in universities which could lead to improvements in e-records management and enhanced service delivery in institutions (Chaputula, 2022; Mphunda and Mnjama, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Data was solicited through interviews from ICT directorates and offices of registrars, and the findings are consistent with the other studies cited above. The study reported that ICT initiatives, including student information management systems, integrated library management systems and financial management systems, are used in creating and capturing records in universities which could lead to improvements in e-records management and enhanced service delivery in institutions (Chaputula, 2022; Mphunda and Mnjama, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Likewise, records management in both Malawian public and private higher education is characterised by an absence of records retention and disposal schedules (Phiri and Tough, 2018; Simwaka, 2022). Mphunda and Mnjama (2022) also assessed the records management programme at Chancellor College through interviews, documentation review and observation, in which findings highlighted approved retention and disposal guidelines were missing from the College. Despite this, the study recommended that the College should archive or destroy obsolete records.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations